Acute Kidney Injury after Complex Endovascular Aneurysm Repair - Liang, Nathan L.; Mohapatra, Abhisekh; Avgerinos, Efthymios D.; Katsargyris, Athanasios (Current Pharmaceutical Design, 2019)
Background: Complex endovascular repair of abdominal aortic aneurysm carries higher perioperative morbidity than standard infrarenal endovascular repair. Objective: This study reviews the incidence and associated factors of acute kidney injury in complex aortic endovascular repair of juxtarenal, pararenal, and thoracoabdominal aortic aneurysms. Methods: A literature review was performed for all studies on the endovascular repair of juxtarenal, pararenal, and thoracoabdominal aneurysms that evaluated rates of acute kidney injury as an outcome. Outcomes were further analyzed by the level of anatomic complexity and method of repair. Results: 52 studies met inclusion criteria, with a total of 5454 individuals undergoing repair from 2004 to 2017. The overall rate of acute kidney injury ranged widely from 0 to 41%, with a rate of hemodialysis from 0 to 19% (temporary) and 0 to 14% (permanent). Increasing anatomic complexity was associated with higher rates of acute kidney injury. Mode of endovascular repair, learning curve effect, and preoperative chronic renal insufficiency did not demonstrate any associations with the outcome. Conclusion: Published rates of acute kidney injury in complex aortic aneurysm repair vary widely with few definitively associated factors other than increasing anatomic complexity and operative time. Further study is needed for the identification of predictors related to postoperative acute kidney injury.
Keywords: aneurysm